(untitled) (Journal of Enam Medical College, 2012)
Chronic pancreatitis is defined as continuing inflammatory disease of pancreas, characterised by irreversible morphological changes leading to pancreatic insufficiency. Chronic pancreatic insufficiency without pancreatitis is also seen in children suffering from cystic fibrosis which is a disease with congenital enzyme deficiency. Mean age of chronic pancreatitis is about 40 years. We present a case of a 9-year-old boy who was diagnosed as a case of chronic calcific pancreatitis. He was admitted with the complaints of paraumbilical pain and vomiting and was found diabetic. Diagnosis was established by X-ray, USG and CT scan of abdomen and ERCP. He was treated surgically in the form of lateral pancreaticojejunostomy (Puestows procedure). DOI: http://dx.doi.org/10.3329/jemc.v2i1.11929 J Enam Med Col 2012; 2(1): 43-45